Α-Haemolysin of Escherichia coli in IBD: a potentiator of inflammatory activity in the colon. Issue 12 (17th February 2014) - Bücker, Roland; Schulz, Emanuel; Günzel, Dorothee; Bojarski, Christian; Lee, In-Fah M; John, Lena J; Wiegand, Stephanie; Janßen, Traute; Wieler, Lothar H; Dobrindt, Ulrich; Beutin, Lothar; Ewers, Christa; et al.
Abstract : Objective: α-Haemolysin (HlyA) influences host cell ionic homeostasis and causes concentration-dependent cell lysis. As a consequence, HlyA-producing Escherichia coli is capable of inducing 'focal leaks' in colon epithelia, through which bacteria and antigens translocate. This study addressed the role of HlyA as a virulence factor in the pathogenesis of colitis according to the 'leaky gut' concept. Design: To study the action of HlyA in the colon, we performed oral administration of HlyA-expressing E coli -536 and its isogenic α-haemolysin-deficient mutant (HDM) in three mouse models: wild type, interleukin-10 knockout mice ( IL-10 −/− ) and monoassociated mice. Electrophysiological properties of the colonised colon were characterised in Ussing experiments. Inflammation scores were evaluated and focal leaks in the colon were assessed by confocal laser-scanning microscopy. HlyA quantity in human colon biopsies was measured by quantitative PCR. Results: All three experimental mouse models infected with HlyA-producing E coli -536 showed an increase in focal leak area compared with HDM. This was associated with a decrease in transepithelial electrical resistance and an increase in macromolecule uptake. As a consequence, inflammatory activity index was increased to a higher degree in inflammation-prone mice. Mucosal samples from human colon were E coli HlyA-positive in 19 of 22 patients with ulcerative colitis, 9 of 9 patients with Crohn's disease and 9 of 12 healthy controls. Moreover, focal leaks were found together with 10-fold increased levels of HlyA in active ulcerative colitis. Conclusions: E coli HlyA impairs intestinal barrier function via focal leak induction in the epithelium, thereby intensifying antigen uptake and triggering intestinal inflammation in vulnerable mouse models. Therefore, HlyA-expressing E coli strains should be considered as potential cofactors in the pathogenesis of intestinal inflammation.